Morpho-functional changes of pituitary-adrenal system in the long-term course of experimental diabetes mellitus - Tkachuk, Yurii (Journal of Education, Health and Sport, 2016)
Tkachuk Yurii. Morpho-functional changes of pituitary-adrenal system in the long-term course of experimental diabetes mellitus. Journal of Education, Health and Sport. 2016;6(4):375-384. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50532 http://ojs.ukw.edu.pl/index.php/johs/article/view/3488 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 25.04.2016. Morpho-functional changes of pituitary-adrenal system in the long-term course of experimental diabetes mellitus Yurii Tkachuk Ivano-Frankivsk National Medical University, Ukraine Summary Different neurohumoral systems are involved in the development and advance of diabetes mellitus as well as its complications, including hypothalamic-pituitary-adrenal system. The increase of functional activity of the latter contributes to the worsening of the disease course and leads to the development of diabetic macroangiopathies (retinopathy, nephropathy). That’s why our goal was to discover common regularities of morpho-functional changes in pituitary-adrenal system in the long-term course of experimental diabetes mellitus (EDM). The investigation involved 20 mature male Wistar rats, which were equally divided into two groups: control group and experimental one. Diabetes mellitus was induced by single dose intraperitoneal administration of streptozotocin (diluted in 0.1 М of citrate buffer with the pH of 4.5) in a dose of 6 mg per 100 grams of body mass. The research work involved the use of histological (hematoxylin-eosin staining, Heidenhain's Azan staining technique) and electron-microscopic investigation methods. We have discovered that on the 56th day of EDM hyperglycemia leads to the increase of functional activity of pituitary-adrenal system that is morphologically manifested in: corticotrophs – as increase of their number, hypertrophy and hyperplasia of structural components of Golgi complex and granular endoplasmic reticulum with the increase in volume ratio of secretory granules, including marginated ones, causing significant increase of ACTH in blood; adrenal cortex – as marked thickening of zona fasciculata and zona reticularis, increase of endocrinocyte area in these zones and lipid droplets in them as well as the increase of blood cortisol level. On the increase of experimental period (day 70) constant hyperfunctioning of pituitary-adrenal system results in its exhaustion. These changes in pituitary are morphologically characterized by ballooning degeneration of corticotrophs, decrease of volume density of secretory granules within them, including the marginated ones, decrease of ACTH in blood; while in adrenal cortex these changes are marked by hydropic degeneration of endocrinocytes of all zones, partial necrosis of endocrinocytes in zona fasciculata, decrease of blood cortisol level. Key words: corticotrophs, adrenal glands, streptozotocin-induced diabetes mellitus.